PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP KEPUASAN PESERTA DIDIK PADA MATA PELAJARAN AKUNTANSI KEUANGAN KELAS XI AKUNTANSI 3 DI SMKN 3 PONTIANAK14 - Novi Suhartiningsih; Warneri Warneri; Okianna Okianna (Universitas Tanjungpura, 2022)
This study aims to examine the effect of teacher Pedagogical Competence on students in FinancialAccounting subjects for class XI Accounting 3 at SMKN 3 Pontianak. This study discussed theteacher's competence on student satisfaction with the research respondents of 37 students fromclass XI Accounting 3 at SMKN 3 Pontianak. The research method is descriptive quantitativemethod. The data is collected through a questionnaire/questionnaire that the reliability has beentested. The data analysis technique used the IBM SPSS Statistics version 25, the results in thisstudy showed that after performing a simple linear regression test on the variables X and Y withthe regression equation, namely Y = 8.091 + 0.663 X and had an effect of 61.3%. Based on thecalculation results of IBM SPSS Statistics version 25, the t-count is 7.448, and the t-table withdegrees of freedom df = n-2 or 37-2 = 35, then the t-table is 2.030. From the results of thecomparison of t-count and t-table, it can be concluded that t-count is 7.448 > t-table is 2.030, soHa is accepted and Ho is rejected. Therefore it was concluded that there was an effect ofPedagogic Competence on student satisfaction in Financial Accounting subjects for class XIaccounting 3 at SMKN 3 Pontianak.Keywords: Pedagogic Competence, Student Satisfaction